The fragmentation of U.S. health care causes and solutions - Elhauge, Einer (New York ; Oxford : Oxford University Press, 2010)
Why is the American health care system so fragmented in the care it gives patients? This title approaches this question and more with a highly interdisciplinary approach. The articles included in the work address legal and regulatory issues, including laws that mandate separate payments for each provider.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Health care reform -- United States